Effectiveness of a multi-strategy intervention in increasing the implementation of vegetable and fruit breaks by Australian primary schools: a non-randomized controlled trial - Nathan Nicole; Wolfenden Luke; Bell Andrew C; Wyse Rebecca; Morgan Philip J; Butler Michelle; Sutherland Rachel; Milat Andrew J; Hector Debra; Wiggers John (BMC, 2012)
Abstract Background Limited evidence exists describing the effectiveness of strategies in facilitating the implementation of vegetable and fruit programs by schools on a population wide basis. The aim of this study was to examine the effectiveness of a multi-strategy intervention in increasing the population-wide implementation of vegetable and fruit breaks by primary schools and to determine if intervention effectiveness varied by school characteristics. Methods A quasi-experimental study was conducted in primary schools in the state of New South Wales, Australia. All primary schools in one region of the state (n = 422) received a multi-strategy intervention. A random sample of schools (n = 406) in the remainder of the state served as comparison schools. The multi-strategy intervention to increase vegetable and fruit breaks involved the development and provision of: program consensus and leadership; staff training; program materials; incentives; follow-up support; and implementation feedback. Comparison schools had access to routine information-based Government support. Data to assess the prevalence of vegetable and fruit breaks were collected by telephone from Principals of the intervention and comparison schools at baseline (2006-2007) and 11 to 15 months following the commencement of the intervention (2009-2010). GEE analysis was used to examine the change in the prevalence of vegetable and fruit breaks in intervention schools compared to comparison schools. Results At follow-up, prevalence of vegetable and fruit breaks increased significantly in both intervention (50.3 % to 82.0 %, p < 0.001) and comparison (45.4 % to 60.9 % p < 0.001) schools. The increase in prevalence in intervention schools was significantly larger than among comparison schools (OR 2.36; 95 % CI 1.60-3.49, p <0.001). The effect size was similar between schools regardless of the rurality or socioeconomic status of school location, school size or government or non-government school type. Conclusion The findings suggest that a multi-strategy intervention can significantly increase the implementation of vegetable and fruit breaks by a large number of Australian primary schools.